Comparison of Bolus and Continuous Infusion of Adrenocorticotropic Hormone During Adrenal Vein Sampling - Hu, Jinbo; Chen, Jiangqiong; Cheng, Qingfeng; Jing, Ying; Yang, Jun; Du, Zhipeng; Song, Ying; Ma, Linqiang; Yang, Yi; Luo, Ting; Wang, Yue; Li, Qifu; et al. (Frontiers in Endocrinology, 2021)
Background: Adrenocorticotropic hormone (ACTH) is widely used in adrenal vein sampling (AVS) and can be administered as a bolus injection or continuous infusion. The optimal administration method has not been determined. We aimed to compare the effects of ACTH bolus with infusion on cannulation success, lateralization assessment and adverse events (AEs). Methods: Retrospectively collected data from patients with primary aldosteronism who underwent AVS with ACTH at a tertiary hospital in China. Rate of successful cannulation, lateralization index (LI), complete biochemical remission and AEs related to AVS were analyzed. Results: The study included 80 patients receiving ACTH bolus and 94 receiving infusions. The rate of successful cannulation was comparable between bolus and infusion groups (75/80, 93.4% vs 88/94, 93.6%). In those with successful cannulation, the bolus group had a higher selectivity index than the bolus group, while LI [6.4(1.8-17.5) vs. 7.6(2.0-27.8), P=0.48] and rate of complete biochemical remission (43/44, 97.7% vs 53/53, 100%, P=0.45) did not significantly differ between the two groups. One in the bolus and one patient in the infusion group had adrenal vein rupture but they recovered with conservative treatment. The bolus group reported more transient AEs such as palpitation (52.9% vs 2.2%) and abdominal discomfort (40.0% vs 2.2%) than the infusion group. Conclusions: Due to their similar effects on cannulation success and lateralization, but a lower rate of transient AEs in the infusion group, the continuous infusion method should be recommended for ACTH stimulation in AVS.